Evaluation of different phosphate organomineral fertilizers in maize cultivation on soils with contrasting phosphorus contents - Paulo César Teixeira; João Augusto Dourado Loiola; Ricardo de Castro Dias; Jorge Makhlouta Alonso; Everaldo Zonta; Rosângela Straliotto (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: Organomineral fertilizers (OMFs) are agronomic inputs combining organic material with mineral fertilizers. The study evaluates the biomass production and P accumulation in maize by applying phosphate OMFs from different organic sources.